Christo and Jean-Claude at UniArt Gallery. The Story behind Prof. Konstantin Valchev’s Collection of Posters (An Interview Made by Dobromira Terpesheva) - Terpesheva, Dobromira (Sledva : NBU Journal of Humanities and Arts, 2020)
UniArt Gallery at the New Bulgarian University held the exhibition Christo and Jeanne Claude Software featuring posters of drawings by Christo for his projects done together with Jeanne Claude. On this occasion, Dobromira Terpesheva speaks with Assoc. Prof. Konstantin Valchev to find out how he got a collection of over 40 posters signed by Christo, and what prompted his idea to exhibit them at the university gallery.